The Immediate Effects of Foam Rolling and Stretching on Iliotibial Band Stiffness: A Randomized Controlled Trial - Talin M Pepper; Jean-Michel Brismée; Phillip S Sizer Jr; Jeegisha Kapila; Gesine H Seeber; Christopher A Huggins; Troy L Hooper (International Journal of Sports Physical Therapy)
# Background